Identification and characterization of tertiary lymphoid structures in murine melanoma - Rodriguez, Anthony B. (Methods Mol Biol, 2018)
Tertiary lymphoid structures (TLS) are transient ectopic lymphoid aggregates that often share structural similarities to conventional secondary lymphoid organs. In a variety of solid cancers, the presence of these structures commonly correlates with high densities of tumor-infiltrating T lymphocytes and prolonged patient survival. These observations suggest that TLS act as sites for the development of beneficial antitumor immune responses. However, few murine tumor models have been described that could enable a more comprehensive understanding of the functionality of TLS in solid cancers. We previously reported that murine B16-F1 melanoma or Lewis Lung carcinoma cells transfected to express the model antigen ovalbumin form intratumoral TLS after implantation into the peritoneal cavity of C57BL/6 mice. In this chapter, we describe immunofluorescent microscopy and flow cytometry approaches for identifying and characterizing intratumoral TLS. Additionally, we describe an adoptive transfer method for demonstrating the infiltration of naïve T cells into B16-OVA melanoma tumors via the lymph node-like vasculature that is an essential functional feature of tumor-associated TLS.